Surgical Management of Mullerian Duct Anomalies - M. El Saman, Ali; A. Velotta, Jennifer; A. Bedaiwy, Mohamed (Current Women's Health Reviews, 2010)
Developmental anomalies of the mullerian duct system represent an interesting field of disorders in obstetrics and gynecology as they can affect any of the reproductive organs from the Fallopian tubes to the hymen. The purpose of this article is to review the available treatment options for mullerian duct anomalies with special emphasis on simple and advanced surgical approaches. Surgical options are presented based on a novel treatment plan classification system adapted from the American Fertility Society classification of mullerian duct anomalies. Care was taken to include all previously termed unclassified anomalies as well as the important category of longitudinal fusion defects. Important diagnostic approaches are discussed with special emphasis on detection of associated anomalies of the urinary system and other relevant systems. Early establishment of an accurate diagnosis is important for planning management options and preventing complications in the genital organs and surrounding systems. Classifying mullerian anomalies based on the available treatment options seems logical and the inclusion of previously unclassified entities is important for a comprehensive understanding and management of this group of disorders. The surgical approach for the correction of mullerian duct anomalies is individualized to the type of malformation. The value of a given surgical procedure should be assessed on terms of its capability to improve a patient's postoperative ability to have healthy sexual relations and achieve successful reproductive outcomes.
Keywords: bicornuate uterus